HISTOLOGICAL EFFECT OF ANTIDIABETIC HERBAL TEA ON THE KIDNEY OF ALBINO RATS INDUCED WITH ALLOXAN (DIABETES) - Uwuigbe , Matthew; OHIWEREI, WISDOM; Obeagu, Emmanuel; Uwuigbe, A.A; Edebiri, Ogbemudia (RADINKA JAYA UTAMA PUBLISHER, 2025)
Background: The kidneys are central to the human excretory system, crucial for maintaining homeostasis. Diabetes mellitus, a prevalent metabolic disorder, commonly leads to serious complications, including diabetic nephropathy. This study investigated the protective effects of an antidiabetic herbal tea on the kidneys of alloxan-induced diabetic albino rats, exploring its potential as a complementary treatment. Methods: Thirty albino rats were randomly assigned to five groups. Group A served as the non-diabetic control. Group B was the untreated diabetic group. Groups C, D, and E were diabetic rats that received varying doses of the herbal tea for 28 days. Body weights were monitored, and kidney tissues were examined via hematoxylin and eosin (H&E) staining to assess histological changes. Results: Untreated diabetic rats (Group B) exhibited significant weight loss and severe renal damage, characterized by interstitial edema, glomerular detachment, and inflammatory cell infiltration. In contrast, the treated groups (C-E) showed dose-dependent renal protection. Group E, receiving the highest dose, displayed the least damage with relatively intact glomeruli. While the herbal tea mitigated weight loss and kidney damage, it did not completely prevent nephropathy, as some tubular basement membrane disorganization persisted. Conclusion: This study confirms that untreated diabetes causes marked weight loss and significant kidney damage. The antidiabetic herbal tea provided a partial protective effect on the kidneys and moderated weight loss in diabetic rats. However, since complete prevention of nephropathy was not achieved, the herbal tea should be considered a beneficial complementary therapy rather than a standalone treatment for managing diabetic complications A concise and factual abstract is required (maximum length of 200 words). The abstract should state briefly the purpose of the research, the principal results, and major conclusions. An abstract is often presented separately from the article, so it must be able to stand alone. References should, therefore, be avoided, but if essential, they must be cited in full, without reference to the reference list. Non-standard or uncommon abbreviations should be avoided, but if essential they must be defined at their first mention in the abstract itself.